Literarische Mehrsprachigkeit und Transkulturalität. Der Dialog zwischen den Kulturen und das Echo von Mimikry und sprachlicher Hybridität im Werk deutsch-türkischer Autorinnen - Brunner, Maria E. (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
The beginnings of migration literature in Germany were noticeable 20 years after the first agreements for work enlistment in the 1950s between countries around the Mediterranean on the one hand and Germany on the other. Well into the 1980s migration literature was considered to be a politically moti-vated, autobiographical and experiential kind of literature produced by migrants, most of whom were initially foreign workers. Today migrant/- migration literature or intercultural literature is considered to be the work of a generation of authors originating from families with migration experience, or migrants themselves. It is the linguistic hybridity and thematic alterity in these works which form the pre-condition for the dialogue between cultures and languages; a dialogue initiated by the successful examples of migration literature currently available on the market. Indeed, a considerable number of German-Turkish authors ’works enrich the cultural and literary scene in Germany. The article analyses the use of hybridity and mimicry as central themes in the novel Der Mond isst die Sterne auf (1998) by Dilek Zapctioglu. This novel is then compared with the stories in the collection Mutterzunge (1998) and with a novel by Emine S. Özdamar, more specifically with the novel Die Brücke vom goldenen Horn (1998), exploring language and thematic hybridization. Central themes in migration literature are issues such as the loss of the homeland, culture shock, alienation, life in and between two languages and cultures, as well as everyday, subliminal discrimination and the accumulating communication problems. The novels can therefore be defined thematically on the basis of their changing time and space coordinates, their shared theme of space diversity, their oscillation between the homeland and the foreign land, the linguistic diversity of their voices and the reflection they offer on the diaspora.